Approach to Lower Limb Oedema - Tiwary, Satyendra K.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book covers all aspects of lower limb oedema including aetiology, pathophysiology, clinical approach, investigations, differential diagnosis and management. It presents all the medical and surgical aspects of lower limb oedema in a well-illustrated manner for better understanding. It covers the lower limb oedema of different origins separately to highlight the different spectrums in their presentation and management. Separate chapters include special conditions like pregnancy, trauma and vascular malformations. The book augments the learning and knowledge for lower limb oedema management by illustrating all aspects of it. It suggests proceeding with every possible aetiology with a better understanding of pathophysiology and adequate designated investigations. It also includes clinical guidelines that help to solve the diagnostic dilemma in lower limb oedema management with infused points to reach a consensus in each and every possible cause. The book includes recent scientific literature and accepted guidelines adopted from the publications during the last ten years to provide latest knowledge in the field. The approaches discussed in the book with specific importance to clinical workup and meticulous investigation protocols will help the surgeons, physicians, primary care workers as well as surgical resident trainees to reach the correct diagnosis and proper management.
Introduction to lower limb oedema -- Anatomy of lower limb -- Epidemiology of lower limb oedema -- Pathophysiology in lower limb oedema -- Aetiology of lower limb oedema -- Clinical examination in lower limb oedema -- Investigations in lower limb oedema -- Differential diagnosis of lower limb oedema -- Acute lower limb oedema -- Chronic lower limb oedema -- Unilateral lower limb oedema -- Deep vein thrombosis -- Chronic venous insufficiency -- Compression stockings -- Imaging in lower limb oedema -- Systemic diseases and lower limb oedema -- Lower limb infection control -- Dermatitis and lower limb swelling -- Pediatric lower limb oedema -- Pregnancy and lower limb swelling -- Lymphoedema -- Medical management of lymphoedema -- Surgical management of lymphoedema -- Genetic association in lower limb swelling -- Complications of lower limb swelling -- Quality of life in lower limb oedema -- Recent advances in management of lower limb oedema.
Keywords: Surgery; Blood-vessels$1 (BSurgery.s; Surgery, Plastic; Orthopedic surgery; Pediatrics; Internal medicine; General Surgery; Vascular Surgery; Plastic Surgery; Surgical Orthopedics; Pediatrics; Internal Medicine